ABUNDANCE AND DISTRIBUTION PATTERN OF THE RAMA (Thalassina anomala) IN THE MANGROVE AREA, GOGOK VILLAGE, MERANTI ISLANDS REGENCY, RIAU PROVINCE - Farona, Fella; Zulkifli, Zulkifli; Efriyeldi, Efriyeldi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2022)
This research was conducted in January 2021 in the Mangrove Area of Gogok Village, Meranti Islands Regency, Riau Province with the aim of knowing the abundance and distribution pattern of Thalassina anomala in the area. The method used is a survey method. Sampling used the line transect method. Sampling was carried out by drawing three transect lines, starting from the lowest low tide line along 45 m inland at each station. carried out on square plots measuring 5x5m. The parameters measured were temperature with an average value of 27.7oC, salinity with an average value of 26.7 ppt, and pH with an average value of 6,8. The results showed that the Thalassina anomala found in the mangrove area of Gogok Village, Meranti Islands Regency, Riau Province was 6.6 ind/25m2. Meanwhile, the distribution pattern of the Thalassina anomala in the area is completely random. The moths live in nests with sediments with low bulk density values, namely on fine-textured soils and granular structures with bulk density values between 0.1 - 0.9 g/cm3. Based on the analysis of organic matter content carried out in the mangrove area of Gogok Village, Meranti Islands Regency, Riau Province, it can be seen that the organic matter content is high between 42,1833 - 58,1833%.